Biodegradation studies of PCP-contaminated soil by cunninghamella bainieri UMAS SD12 and trichoderma harzianum UMAS SD14 - Shahirah Najiha, Binti Hassan (unimas, 2014)
The activity of lignin peroxidase, manganese peroxidase, and laccase were investigated in the biodegradation of pentachlorophenol (PCP) by two species of fungi; Cunninghamella bainieri UMAS SD12 and Trichoderma harzianum UMAS SD14 within a period of 25 days in soil immobilized with sago hampas. The depletion of pentachlorophenol concentration from cultures of both species of fungi was observed. All three ligninolytic enzymes; lignin peroxidase (LiP), manganese peroxidase (MnP), and laccase (Lac) were detected in C. bainieri and T. harzianum. Therefore, from the results obtained, PCP was degraded under ligninolytic as well as in nonligninolytic conditions. By comparing between two different of fungi, C. bainieri was able to degrade PCP more effectively with 10.67% of residual PCP concentration compared to T.harzianum with 13% of residual PCP concentration within a period of 25 days